OPPRESSION TOWARD WOMEN REFLECTED IN FEMALE CHARACTERS IN DRAMA THE CONDUCT OF LIFE (1985) BY MARIA IRENE FORNES AS A FEMINISM STUDY - Nurul Aminah; Yulistiyanti Yulistiyanti (Universitas Stikubank (UNISBANK) Semarang, 2022)
Abstract The study reveals woman oppression in The Conduct of Life by Maria Irene Fornes. The purpose of this paper is to describe feminist character of Maria Irene Fornes’s The Conduct of Life by analyzing the female character. This study applied qualitative study and applied feminist theory of Kate Millet (1969) in her book entitled Sexual Politics. The data were collected by reading the text of drama comprehensively and taking some notes on important words, sentences, and narration that relate to the topic. After analyzing the data, it can be concluded that the female character in Maria Irene Fornes The Conduct of Life accepted oppression because of the low level of law that imposed in the 19th century, disregarding of society that is known as patriarchy. The oppression that the female characters get is verbal oppression and physical abuse (sexual abuse). Keywords: Sexual Politics, Kate Millet, the Conduct of Life, Maria Irene Fornes, Woman Oppression